Effect of different restorative design on stress concentration of lithium disilicate and monolithic zirconia endocrown on a mandibular molar - a finite element analysis - Garima Karn; Manoj Shetty; Chethan Hegde (BMC Oral Health)
Abstract Background The purpose of this simulation study was to evaluate effect of different restorative design on stress concentration of endocrown. Different restorative materials were used on a mandibular molar using a finite element analysis. Methods A 3D FEA model of mandibular molar was constructed using the average values and was used in this analysis. 2 materials were used which were lithium disilicate and zirconia and 2 different margin design of knife edge and shoulder margins were used in various combinations of material and margin design. A constant 12° of internal wall angulation was considered for all the 4 models and a uniform cement thicknes of 100 μm was considered. A uniform 2 mm of bulk fill composite was used as a base beneath the endocrowns. 300 N load was applied on the cusps for each model and linear static analysis was carried out. Results Endocrowns of lithium disilicate was found to exert a greater stress concentration in comparison to zirconia endocrowns in both the margin designs of knife edge and shoulder. Knife edge margins were seen to yield greater stress concentration on the remaining tooth structure in comparison to shoulder margins in endocrowns of both the materials used. Conclusion There is a positive influence of margin design selection within the same material used for the fabrication of endocrown.